A Challenging Treatment Decision for a Rare Association: Case Report of Familial Turcot Syndrome With Fistulizing Crohn’s Disease - Corbera-Hincapie, Montserrat; Beasley, Genie L. (Frontiers in Pediatrics, 2018)
Turcot syndrome and fistulizing Crohn’s Disease are two disease entities that are not usually associated with one another, particularly given the rarity of the former. Management of patients who have this rare combination of disease processes can present several challenges, as surgical options may be limited and immunosuppression to treat one may lead to accelerated progression of malignancy in the other. This unique case highlights the importance of weighing the risks and benefits involved in treating two disease entities that impact one another.